2009
DOI: 10.1186/1471-2350-10-25
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of pathogenetic MC4R mutations in Italian children with early Onset obesity, tall stature and familial history of obesity

Abstract: Background: Melanocortin-4-receptor (MC4R) mutations represent the most frequent genetic cause of non-syndromic early onset obesity. Children carrying MC4R mutations seem to show a particular phenotype characterized by early onset, severe obesity and high stature. To verify whether MC4R mutations are associated with this particular phenotype in the Italian pediatric population, we decided to screen the MC4R gene in a group of obese children selected on the basis of their phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…However, the MC4R rs17782313 polymorphism did not reach the statistical significance as it had a lesser effect in this population and, even though a similar trend was observed. While several studies have reported statistically significant associations between the MC4R rs17782313 and BMI or obesity [2], [24], [25], [51], there are also studies that did not find a significant association [9], [52] or found stronger associations with weight than BMI [11] and even studies that have reported an association with higher height [9], [53], [54] and that this association may mask the effects on BMI despite being associated with higher weight. Our results are in agreement with this observation as we found statistically significant differences in weight and height (although very small in magnitude for height).In agreement with other studies [12], [13] we have also found additive effects of these polymorphisms in this population.…”
Section: Discussionmentioning
confidence: 99%
“…However, the MC4R rs17782313 polymorphism did not reach the statistical significance as it had a lesser effect in this population and, even though a similar trend was observed. While several studies have reported statistically significant associations between the MC4R rs17782313 and BMI or obesity [2], [24], [25], [51], there are also studies that did not find a significant association [9], [52] or found stronger associations with weight than BMI [11] and even studies that have reported an association with higher height [9], [53], [54] and that this association may mask the effects on BMI despite being associated with higher weight. Our results are in agreement with this observation as we found statistically significant differences in weight and height (although very small in magnitude for height).In agreement with other studies [12], [13] we have also found additive effects of these polymorphisms in this population.…”
Section: Discussionmentioning
confidence: 99%
“…The different criteria for obesity definition led to varied obese and nonobese groups, which were applied to estimate the OR without any correction. Different cutoff points (28,30,35,40 kg/m 2 , or 95th, 97th, 98th BMI percentile) were used for cases, whereas cutoff points (25, 22, or 30 kg/m 2 ) for controls varied as well. Besides, different sex ratios and age of individuals among studies might influence the effect magnitude of the V103I variant on obesity.…”
Section: Figurementioning
confidence: 99%
“…This mutation was found several times in both obese and lean populations (Lubrano-Berthelier et al 2003, Hainerova et al 2007, Nowacka-Woszuk et al 2011. This fact indicates that it may be one of the most prevalent MC4R mutations in Europe (Valli-Jaakola et al 2004, Hainerova et al 2007, Santoro et al 2009, Nowacka-Woszuk et al 2011.…”
Section: Mc4r Genotypesmentioning
confidence: 99%